HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT KEPATUHAN MINUM OBAT PADA PASIEN CONGESTIVE HEART FAILURE (CHF) - Lian Setiawati D. Rahmatola; Ismunandar Wahyu Kindang; Matius Paundanan (KEWINUS: Jurnal Keperawatan dan Kesehatan, 2024)
Congestive Heart Failure (CHF) patients require medication adherence to prevent recurrence or worsening of the condition. Treatment compliance in CHF patients requires family support. The purpose of the study was to determine the relationship between family support and the level of compliance with taking medication in CHF patients in the ICVCU room at RSUD Anutapura Palu. This type of research is quantitative with an analytic approach using a cross-sectional design. The population in this study were CHF patients in the ICVCU room at RSUD Anutapura Palu from March to May 2024, totaling 53 respondents, with a sampling technique using puposive sampling of 35 patients. The results of the study supportive family support as many as 18 respondents and those who did not support as many as 17 respondents while for the level of compliance with taking high medication as many as 13 respondents, moderate compliance as many as 11 respondents and for low compliance as many as 11 respondents. The results of statistical analysis using the Chi-square correlation test obtained from 35 respondents showed a p-value of 0.033 (p <0.05). There is a relationship between family support and the level of compliance with taking medication in CHF patients in the ICVCU room at RSUD Anutapura Palu. It is expected to be input for hospitals to always provide education to patients to always take medicine and families always provide support in treatment.